Clinico-pathological effects of bracken fern (Pteridium aquilinum) feeding in laboratory rats - Gounalan, S; Somvanshi, R; Kumar, Ram; Dash, S; Devi, V (The Indian Journal of Animal Sciences, 2012)
Experimental studies with bracken fern @25 % in concentrate ration mixture were conducted in rats. Fern fed rats showed progressive anaemia, leukopaenia, lymphopaenia and relative neutrophilia. A significant elevation in serum enzymes like SGOT, SGPT, ALP, mea and creatinine was seen. Histopathologically rats showed mild oedema in brain, mild to moderate vascular changes in most of visceral organs, vacuolar degenerative changes in hepatocytes, hypersecretory activity in intestine, engorged red pulp with haemosiderosis in spleen and degenerative changes in testes. Low level of toxic principle ptaquiloside was detected in bracken ferns by TLC and HPLC methods.